BAG2 ameliorates endoplasmic reticulum stress-induced cell apoptosis in Mycobacterium tuberculosis-infected macrophages through selective autophagy. Issue 8 (2nd August 2020) - Liang, Shuxin; Wang, Fengyu; Bao, Changlei; Han, Jing; Guo, Ying; Liu, Fayang; Zhang, Yong
ABSTRACT: BAG2 (BCL2 associated athanogene 2) is associated with cell fate determination in response to various pathological conditions. However, the effects of BAG2 on M. tuberculosis -induced endoplasmic reticulum (ER) stress remain elusive. Herein, we report that M. tuberculosis infection of macrophages triggered ER stress and downregulated BAG2 expression. Overexpression of BAG2 enhanced autophagic flux and activated macroautophagy/autophagy targeted to the ER (reticulophagy). In addition, through increasingly localizing SQSTM1 to the ER in BAG2-overexpressing macrophages, we found that the autophagy receptor protein SQSTM1/p62 (sequestosome 1) is associated with the BAG2-induced reticulophagy. Our data also confirmed that BAG2 could render cells resistant to M. tuberculosis -induced cellular damage, and the anti-apoptotic effects of BAG2 in M. tuberculosis -treated macrophages were partially abolished by the autophagic flux inhibitor bafilomycin A1 . Furthermore, the dissociation of BECN1 and BCL2 mediated by activation of mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) was responsible for BAG2-activated autophagy. In addition, XBP1 downstream of the ERN1/IRE1 signaling pathway was bound to the Bag2 promoter region and transcriptionally inhibited BAG2 expression. Collectively, these results indicated that BAG2 has anti-apoptotic effects on M. tuberculosis -induced ER stress, which is dependent on the promotion of autophagic flux and the induction of selective autophagy. We revealed a potential host defense mechanism that links BAG2 to ER stress and autophagy during M. tuberculosis infection. Abbreviations: ATF6: activating transcription factor 6; BECN1: beclin 1; Baf A1: bafilomycin A1 ; CASP3: caspase 3; DDIT3/CHOP/GADD153: DNA damage inducible transcript 3; DAPI: 4ʹ, 6-diamidino-2-phenylindole; EIF2AK3/PERK: eukaryotic translation initiation factor 2 alpha kinase 3; ER: endoplasmic reticulum; ERN1/IRE1: endoplasmic reticulum to nucleus signaling 1; HSPA5/GRP78/BiP: heat shock protein 5; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MAPK/ERK: mitogen-activated protein kinase; SQSTM1/p62: sequestosome 1; UPR: unfolded protein response; XBP1: x-box binding protein 1